Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1074/jbc.m110.174706
|View full text |Cite
|
Sign up to set email alerts
|

PTPD1 Supports Receptor Stability and Mitogenic Signaling in Bladder Cancer Cells

Abstract: PTPD1, a cytosolic non-receptor protein-tyrosine phosphatase, stimulates the Src-EGF transduction pathway. Localization of PTPD1 at actin cytoskeleton and adhesion sites is required for cell scattering and migration. Here, we show that during EGF stimulation, PTPD1 is rapidly recruited to endocytic vesicles containing the EGF receptor. Endosomal localization of PTPD1 is mediated by interaction with KIF16B, an endosomal kinesin that modulates receptor recycling at the plasma membrane. Silencing of PTPD1 promote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
43
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 37 publications
(46 reference statements)
3
43
0
Order By: Relevance
“…Cardone et al reported that PTPN21 is recruited to mitochondria by binding the scaffold protein AKAP121 and that this interaction is essential for the phosphatase dependent dephosphorylation of the inhibitory tyrosine 527 of the SRC kinase (Cardone et al, 2004; Carlucci et al, 2010). …”
Section: Resultsmentioning
confidence: 99%
“…Cardone et al reported that PTPN21 is recruited to mitochondria by binding the scaffold protein AKAP121 and that this interaction is essential for the phosphatase dependent dephosphorylation of the inhibitory tyrosine 527 of the SRC kinase (Cardone et al, 2004; Carlucci et al, 2010). …”
Section: Resultsmentioning
confidence: 99%
“…This strategy identified 28 overlapping targets, of which four overlapping candidate gene targets (DICER1, UBE4B, SGPP1, and PTPN21) were further analyzed based upon their potential involvement in radiation resistance or oncogenic processes (11,(25)(26)(27)(28). Using qRT-PCR, we verified that their expression were significantly decreased in PC3-miR-95 cells relative to PC3-control cells (Fig.…”
Section: Mir-95 Promotes Radiation Resistance Through Downregulation mentioning
confidence: 91%
“…PTPN21over-expression is thought to be an early step in urothelial cancer progression. In terms of expression in vivo, PTPN21 is absent from the normal bladder tissue, hyperplastic urothelium, and urothelial papilloma, whereas its expression gradually increases from low grade to high grade urothelial carcinoma (103).…”
Section: Renal Cell and Bladder Cancermentioning
confidence: 99%